Carbon cycling dynamics in the seasonal sea‐ice zone of East Antarctica. Issue 12 (19th December 2016) - Roden, Nicholas P.; Tilbrook, Bronte; Trull, Thomas W.; Virtue, Patti; Williams, Guy D.
Abstract: The carbon cycle of the seasonally ice covered region of the southwest Indian Ocean sector of East Antarctica (30°–80°E, 60°–69°S) was investigated during austral summer (January–March 2006). Large variability in the drivers and timing of carbon cycling dynamics were observed and indicated that the study site was a weak net source of carbon dioxide (CO2 ) to the atmosphere of 0.8 ± 1.6 g C m −2 during the ice‐free period, with narrow bands of CO2 uptake observed near the continental margin and north of the Southern Antarctic Circumpolar Current Front. Continuous surface measurements of dissolved oxygen and the fugacity of CO2 were combined with net community production estimates from oxygen/argon ratios to show that surface heat gain and photosynthesis were responsible for the majority of observed surface water variability. On seasonal timescales, winter sea‐ice cover reduced the flux of CO2 to the atmosphere in the study area, followed by biologically driven drawdown of CO2 as the ice retreated in spring‐summer highlighting the important role that sea‐ice formation and retreat has on the biogeochemical cycling of the region. Key Points: Large variability in the biological and physical drivers of carbon cycling dynamics was observed The East Antarctic seasonal ice zone was a weak net source of CO2 to the atmosphere during the ice‐free period Seasonally integrated estimates of net community production were as high as 6.4 mol C m −2, but on average were found to be 1.3 ± 0.9 mol C m −2